MANAGEMENT OF INTERNAL QUALITY ASSURANCE SYSTEM OF HIGHER EDUCATION - Siagian, Yosua Marasi Parningotan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
The level of knowledge of university residents regarding the internal quality assurance system (SPMI) of higher education at Tanjungpura University is still at a low level and needs to be developed before the formation of an internal quality assurance system for educational units. Apart from that, educators' understanding is closely related to national education standards and their duties are still at a sufficient level so there is still a need to increase understanding in order to be able to carry out processes and evaluations in accordance with the standards. There is a need for development of teaching and education staff in terms of knowledge and skills in implementing internal quality assurance through special teams from outside the education unit to schools who are ready to be able to implement an internal quality assurance system. To be able to guarantee the quality of education, educational units need to form SPMI according to applicable standards and regulations. Even though the National Higher Education Standards (SNPT). seen from the accreditation score that reaches the highest standards. For this reason, studies are needed regarding the internal quality assurance system at the University so that it can gradually meet the SNPT or even exceed it